The Impact Of Green Human Resource Management On Evironmental Performance: Systematic Literature Review With Hybrid Method - Alma Syifa Maulidina; Muhammad Deny (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
Climate change and environmental issues are increasingly becoming major concerns worldwide, with impacts increasingly felt across various industrial sectors. In this context, corporate social responsibility (CSR) and corporate social responsibility (CSR) are two inseparable elements in efforts to create a greener and more sustainable future. One increasingly popular way to address these challenges is through the implementation of Green Human Resource Management (GHRM), which focuses on integrating environmentally friendly principles into human resource management (HRM) (Renwick et al., 2013). This article aims to examine the development of the Green Human Resource Management concept, the main practices implemented by companies within a biodiversity framework, and the benefits that can be obtained from implementing GHRM. Researchers also function as a literature research tool, so the level of objectivity is still debatable. The explicit search process means that SLR is usually more time-consuming than traditional observation (Priharsari, 2022). This step is in accordance with the guidelines in PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The literature search was conducted using the Watase UAKE application by entering the Scopus search engine API key. The search engine was selected to obtain reputable scientific literature indexed by Scopus Q1, Q2, Q3, and Q4. SLR research can be used as a method to identify and uncover theories on the topic of interest. Based on the 194 articles reviewed, a systematic literature review was conducted, with publication dates between 2020 and 2024. Only 40 articles met the criteria and were used as references in this study. Based on the findings, the most widely used research method was quantitative. The results also indicate that Green HRM plays a significant role in Environmental Performance, which is widely applied within organizations and the business world.